Gender-related propensity score match analysis of ECMO therapy in postcardiotomy cardiogenic shock in patients after myocardial revascularization. (July 2022) - Gerfer, Stephen; Gaisendrees, Christopher; Djordjevic, Ilija; Ivanov, Borko; Merkle, Julia; Eghbalzadeh, Kaveh; Schlachtenberger, Georg; Rustenbach, Christian; Sabashnikov, Anton; Kuhn-Régnier, Ferdinand; Mader, Navid; Wahlers, Thorsten
Background: Gender is known to influence the pathophysiology and pathogenesis of the coronary vascular disease. Data on gender-related differences in patients with veno-arterial extracorporeal membrane oxygenation due to postcardiotomy cardiogenic shock is lacking in current literature. We aimed to analyze the impact of gender on intraoperative and short-term outcomes of vaECMO patients after coronary surgery and postcardiotomy cardiogenic shock. Methods: Between 2006 and 2017, a total of 92 patients with PCS after CABG underwent vaECMO-implantation at our institution. After a 1:1 propensity score match (PSM) for relevant preoperative data, we identified a cohort of 32 patients, 16 males, and 16 females. Periprocedural and short-term outcome data were analyzed with respect to sex differences. Results: The mean age was 64 ± 11 years, and 79% ( n = 73) were male patients. Clinical outcomes showed a 30-day all-cause mortality of 64% ( n = 59). After PSM, male patients showed a significantly smaller number of arterial grafts (0.4 ± 0.53 male vs 1.1 ± 0.7 female; p = 0.037). Thirty-day all-cause mortality did not differ between the groups (56% male vs 75% female; p = 0.262). In general, short-term outcome data were comparable without significant differences for the matched groups. Conclusion: Gender has no impact on patients with vaECMO therapy due to PCS in isolated coronary surgery.